Incongruencias entre al art. 384 del código integral penal respecto de las contravenciones de tránsito y la constitución de la república del ecuador - Alarcon Parrales, Dayse Noemi (2014)
Recently issued the Code of Criminal Integral stipulating several traffic violations, including that referred to in Article 384 which states: "Driving a vehicle under the influence of narcotics, psychotropic substances or preparations that containing.- The person who drives a vehicle under the influence of drugs, psychotropic or preparations containing substances, shall be punished with fifteen points reducing your driving license and thirty days' imprisonment; also as a preventive measure apprehend the vehicle for twenty-four hours. " That is, it has been criminalized with imprisonment of thirty days, a person driving the vehicle under the influence of drugs, psychotropic or preparations containing substances, contrary expressly stipulated in Art. 364 of the Constitution of the Republic of Ecuador, which commands: "addictions are a public health problem. The State shall be responsible for developing coordinated information programs, prevention and control of alcohol, snuff and drugs and psychotropic substances; and provide treatment and rehabilitation to occasional, regular and problem users. In no event shall they be criminalized nor their constitutional rights violated. The State shall control and regulate the advertising of alcohol and snuff. "Ie can not violate the right to freedom of a person suffering from addiction, because it contradicts the constitutional provision. Given this unlegal and unconstitutional situation should reform the Art. 384 of the Code of Criminal Integral to this violation of traffic is eliminated.